An exploration of N-heterocyclic carbene-based Ir(III) complexes for phosphorescent organic light-emitting diode applications. (December 2015) - Cho, Woosum; Yoon, Juho; Sarada, Ganguri; Giridhar, Thota; Liu, Yuan; Jiang, Zuo-Quan; Son, Young Hoon; Kang, Byoung Yeop; Kwon, Jang Hyuk; Jin, Sung-Ho
Abstract: Two new blue emitting heteroleptic Ir(III) complexes containing a difluorophenylmethylpyridine (fpmpy)-based main ligand and a carbene-based ancillary ligand were synthesized: bis[2-(4, 6-difluorophenyl)-4-methylpyridinato-C2, N](1′-(4′-fluorophenyl)-3′-methylbenzimidazole)iridium(III) and bis[2-(4, 6-difluorophenyl)-4-methylpyridinato-C2, N](1′-methyl-3′-phenylbenzimidazole)iridium(III). The synthesis, X-ray crystal structures, photophysical and electrochemical properties, and PhOLED performance of both Ir(III) complexes are described. The two Ir(III) complexes showed very similar UV–visible absorption spectra irrespective of the presence of the fluorine atom in the ancillary ligand. The photoluminescence spectrum of the complex with the additional fluorine atom showed double emission bands at 464 and 482 nm in dichloromethane solution, whereas the alternate complex, without the extra fluorine atom, only exhibited a single emission at 487 nm. Both Ir(III) complexes were utilized for blue PhOLEDs with an identical device configuration. The complex with the additional fluorine atom exhibited an external quantum efficiency of 4.2%, which was higher than that of the alternate complex (3.5%). Highlights: Two Ir(III) complexes with an N -heterocyclic carbene as third CˆC ligand with/without –F were synthesized. Investigated the effect of an N -heterocyclic carbene with/without –F in blue OLEDs. Key changes were found in PL and EL (OLED) properties.